The Bone Houses - Lloyd-Jones, Emily (New York ; Little, Brown and Company, 2019)
"When risen corpses called 'bone houses' threaten Ryn's village because of a decades-old curse, she teams up with a mapmaker named Ellis to solve the mystery of the curse and destroy the bone houses forever"--
Keywords: Dead -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Cartographers -- Juvenile fiction; Supernatural -- Juvenile fiction; Gravediggers -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Dead -- Fiction; Blessing and cursing -- Fiction; Cartographers -- Fiction; Supernatural -- Fiction; Gravediggers -- Fiction; Brothers and sisters -- Fiction; Fantasy